Kemampuan Material Akustik dari Pelepah Pisang dan Sabut Kelapa sebagai Peredam Kebisingan - Annisaaul Lathiifah (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2021)
As technology develops, it causes more and more equipment which can mostly trigger noise. Acoustic materials can be used to reduce noise because they reduce sound. The purpose of this research is to determine the sound absorption coefficient of the acoustic material from banana stems and coconut coirs. Six samples were made and tested using a resonator space to test the sound absorption coefficient. The test results reveal that the sound absorption coefficient is influenced by the thickness of the sample. The sound absorption coefficient for each sample at a frequency of 500 Hz is 0,03836; 0,02359; 0,02139; 0,01971; 0,01631; 0,01069. The best sample in this study is sample 1 which has a sound absorption coefficient of 0,03836 which is the highest compared to other samples.